2005
DOI: 10.1051/0004-6361:20052800
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of V838 Monocerotis during and after the 2002 eruption

Abstract: Abstract. By fitting the available photometric data on V838 Mon with standard supergiant spectra we have derived principal stellar parameters, i.e. effective temperature, radius and luminosity, and followed the evolution of the object since its discovery in early January 2002. Our analysis shows that the 2002 outburst of V838 Mon consisted of two major phases: pre-eruption, which was observed in January 2002 and a major outburst, the eruption, which started in the beginning of February 2002. During pre-eruptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
166
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(186 citation statements)
references
References 24 publications
20
166
0
Order By: Relevance
“…The object was then significantly cooler however than before the outburst (early M-type spectrum versus K1-2). The latter agrees with what was observed in V838 Mon and V4332 Sgr, displaying M-type spectra several years after their outbursts (Tylenda 2005;Tylenda et al 2005). However, the drop in luminosity of V1309 Sco was unexpectedly deep.…”
Section: Merger-powered Outburst -Mergerburstsupporting
confidence: 90%
See 1 more Smart Citation
“…The object was then significantly cooler however than before the outburst (early M-type spectrum versus K1-2). The latter agrees with what was observed in V838 Mon and V4332 Sgr, displaying M-type spectra several years after their outbursts (Tylenda 2005;Tylenda et al 2005). However, the drop in luminosity of V1309 Sco was unexpectedly deep.…”
Section: Merger-powered Outburst -Mergerburstsupporting
confidence: 90%
“…7. They show that the evolution of V1309 Sco during outburst and decline was really of the same sort as those of V838 Mon (Tylenda 2005) and V4332 Sgr . In all these cases the main decline in luminosity was accompanied by a decline in the effective temperature.…”
Section: Observed Evolutionmentioning
confidence: 84%
“…Therefore M 31 RV is the only object for which we can be confident of its maximum luminosity of ∼8 × 10 5 L (Mould et al 1990). For a distance to V838 Mon of 8 kpc the maximum luminosity of this object was ∼1.2 × 10 6 L (Tylenda 2005). However, because of distance uncertainties this value is probably uncertain by a factor of ∼2.…”
Section: Observed Propertiesmentioning
confidence: 83%
“…V838 Mon, after having reached its coolest state, kept declining in luminosity but at a much slower rate and with a slowly increasing effective temperature. About 1000 days after eruption the object was ∼40 times fainter than at maximum, with T eff 2600 K corresponding to a spectral type of ∼M 6 (Tylenda 2005). At ∼3500 days after eruption V4332 Sgr decreased by a factor of ∼1500 in luminosity, its spectral type was then ∼M 3 and T eff 3400 K (Tylenda et al 2005a).…”
Section: Observed Propertiesmentioning
confidence: 95%
“…classical novae), was that the object evolved to progressively lower effective temperatures and declined as a very late M-type supergiant (e.g. Tylenda 2005). Tylenda & Soker (2006) showed that the eruption of V838 Mon cannot be explained by a thermonuclear runaway similar to classical novae, nor by a late He-shell flash.…”
Section: Introductionmentioning
confidence: 99%